On the class of analytic functions defined by Robertson associated with nephroid domain - SIVASUBRAMANIAN, Kavitha (Studia Universitatis Babeș-Bolyai Mathematica, 2025)
The primary focus of this article is to explore a novel subclass, denoted as GNGN, of analytic functions. These functions exhibit starlike properties concerning a boundary point within a nephroid domain. The author obtains representation theorems, establishes growth and distortion theorems, and investigates various implications related to differential subordination. In addition to the investigation of coefficient estimates, the study also explores specific consequences of differential subordination. Mathematics Subject Classification (2010): 30C45, 33C50, 30C80. Received 12 September 2023; Accepted 29 March 2024.